School Leadership Roles in Developing Islamic Teachers’ Pedagogical Competence: Peran Kepemimpinan Sekolah dalam Mengembangkan Kompetensi Pedagogis Guru Islam - Rahmawati, Harum Puteri; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2025)
Background: School leadership plays a crucial role in shaping teachers’ pedagogical quality, especially in Islamic education settings. Specific Background: In Indonesia, many Islamic Education teachers still struggle to meet pedagogical standards due to limited guidance and motivation from school leaders. Gap: Few studies have explored how principals in public schools support the development of Islamic Education teachers’ competencies through practical leadership strategies. Aims: This study aims to describe the principal’s role in improving pedagogical competence and identify challenges faced in the process. Results: The findings reveal that the principal acts effectively as a leader, facilitator, motivator, and resource manager, although challenges arise from limited resources and lengthy administrative processes. Novelty: The study provides a contextual insight into Islamic school leadership practices at the junior high level. Implications: The results emphasize the need for continuous leadership training and professional support systems to strengthen Islamic Education quality. Highlights:• School leadership enhances Islamic teachers’ pedagogical competence• Professional development requires strong administrative support• Collaboration and communication are key in teacher capacity building Keywords: School Principal, Pedagogical Competence, Islamic Education, Teacher Development, Leadership